Contribution of Senior Citizen Allowance in Elderly Livelihoods in Beldandi - Bam, Nirmala Kumari (AMC Journal (Dhangadhi), 2026)
This study examines the contribution of Nepal’s Senior Citizen Allowance (SCA) to elderly livelihoods in Beldandi, utilizing a mixed-methods approach with data from 216 respondents. Findings indicate that SCA is a critical source of income, with 33.3 percent of elders relying solely on it and 38.9 percent combining it with family support. Expenditure patterns show that the allowance is primarily used for basic needs: food (40.3%) and healthcare (29.0%). While the majority (61.1%) reported the allowance as only partially adequate, it significantly enhanced living standards for 75 percent of recipients and boosted social participation evidenced by increases in community meeting attendance (from 28.7% to 52.3%) and religious activities (from 35.6% to 63.9%). The SCA also reinforced dignity and social security, with 53.7 percent of respondents noting increased family respect and 74 percent reporting a moderate to strong sense of financial security. However, challenges persist, including delays in disbursement (56.5% experienced delays), long queues (31.5%), and mobility issues. Key suggestions from beneficiaries include increasing the allowance amount (40.7%) and ensuring timely distribution (28.7%). In conclusion, the Senior Citizen Allowance is crucial for agency and welfare of elderly people in rural Nepal, though upgrades in the timeliness, accessibility and value of the allowance are necessary to increase its efficiency of use in social protection.